Detection of Antibacterial Residues in two types of fish in Shatt Al-Arab river, Southern Iraq - Ahmed, Mayada; Resen, Amjad; Al- Niaeem, Khalidah (Iraqi Journal of Aquaculture, 2024)
The presence of Antibacterial in the aquatic environment is a major concern because of the effect of Antibacterial on water quality, aquatic organisms and human health. The current study aims to detect Antibacterial (Amoxicillin, Ciprofloxacin, and Levofloxacin) Seasonally in the muscles and liver of two types of fish (Oreochromis niloticus) and (Planiliza abu) during the period from November 2020 to August 2021 in two selected stations in Shatt Al-Arab, Basrah, Iraq. The samples were analyzed using high performance liquid chromatography (HPLC), High concentrations of antibiotics were recorded in the muscles and liver of fish during the study period. The highest concentration of antibiotics Amoxicillin (AMO) was recorded in the muscles of Nile tilapia during the spring season (8.7 mg. kg-1). Antibiotic concentrations Ciprofloxacin (CIP) were also high in most seasons of the study. The presence of Antibacterial in the aquatic environment in such high concentrations is a source of great concern. The study recommends conducting more studies to measure Antibacterial contamination in other areas of the Shatt Al-Arab and the Iraqi marshes.